Mobile health education for salt reduction and hypertension prevention: effects on knowledge acquisition and behavioral change among Chinese third-grade students - Zhang, Yang; Lin, Jiajin; Qu, Chen; Mao, Tao; Zhong, Jiao; Yuan, Xin; Liu, Yan; Zhen, Shiqi (Frontiers in Public Health, 2025)
Background and aimsThis study evaluates the impact of a comprehensive health education intervention delivered via a mobile application on health knowledge and behavior among third-grade students in Zhenjiang, Jiangsu Province, China. With increasing rates of non-communicable diseases, particularly hypertension among children, this intervention aimed to enhance health literacy and promote healthier behaviors.MethodsA total of 15,656 students from 88 primary schools participated, with 11,614 completing both pre- and post-intervention surveys. The intervention included 20 animated health education lessons covering topics such as balanced diets, personal hygiene, and salt reduction, alongside activities involving parents and school staff.ResultsResults indicated significant improvements in health knowledge, with an average increase of 5.6 points, and health behavior scores increased by 2.6 points post-intervention. The awareness of key knowledge areas, including vision protection and correct coughing/sneezing habits, had increased by more than 10%. However, improvements in health behaviors were less pronounced, underscoring the challenge of translating knowledge into action. A mixed-effects model analysis revealed that baseline scores significantly influenced post-intervention outcomes, with urban students outperforming their rural counterparts.ConclusionThis study highlights the effectiveness of mobile health education interventions in enhancing health literacy among children and suggests the need for continued focus on behavior change strategies to complement knowledge acquisition.